SOSIALISASI BIJAK MENGGUNAKAN INTERNET KEPADA KOMUNITAS IBU RUMAH TANGGA ANGGOTA IKBI PTPN III SEI MANGKE - Rizkha Rida; Muhammad Fiza Lubis; Margie Subahagia Ningsih; Li Idiil Fitri; Suci Ayu Lestari (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2024)
This community service aims to help the community increase insight into the use of digital media and ethics in using social media for mothers who are members of the IKBI (Ikatan Keluarga Besar Istri) PTPN III Sei Mangke through outreach. Mothers can innovate to carry out businesses or business activities using internet media and those related to the digital world. Then what the author will discuss in community service is how to respond to technological advances because in the current millennial era it is very vulnerable to cyber crimes and bullying which are currently rampant on every existing social media, in order to earn money. Many content creators/digital artists make viral videos using YouTube media, and of course the aim is to find an audience and earn money. With this, sometimes there are a lot of irregularities, namely: creating fake news/Hoaxes, pitting people against each other, defaming someone's good name through uploaded content. So it is very closely related to the ITE Law, which can lead to criminal acts.